Transnational households in the context of female migration from Slovakia to Austria - Sekulová, Martina (Lidé města, 2013)
The article concentrates on transnational care-giving practises of Slovak women providing home elder care in Austria related to production and consumption in their families in Slovakia. The article focuses on how trans-border migration influences care-giving, organisation of the household and family practises in domestic workers' families in Slovakia. My argument is that in order to understand deeper contexts and consequences of transnational migration of domestic workers in private households we must consider gender as a complex multi-dimensional category. The emphasis of the article is put on how women reflect and manifest their gender identity and how "ways of doing family" are gendered in transnational families of Slovak elder care providers. Theoretical starting points for analysis are a transnational approach and gender perspective.